Voice, acountability and fiscal descentralization : The case of Chilean municipal education - Letelier S., Leonardo (2013)
At the beginning of the 80s, the Chilean government handed over the administration of public schools to municipal governments and established a voucher per student type of funding. By running an empirical model that uses a panel of municipal observations between 2005 and 2011, we intend to explain the average municipal score achieved by public schools on the so called "SIMCE" test, which measures math and language skills at the 4th degree. Our empirical analysis suggests that; i) more "fiscally empowered" and "accountable" local governments perform better, ii) competition from publicly funded private schools enhances municipal schools' performance, iii) benefits from decentralization appear to diminish as the number of schools per municipal jurisdiction raises and, iv) socio economic variables are globally and individually significant.